Comparative Literature: A Cure for an Inferiority Complex? - Gjurgjan, Ljiljana Ina (Array, 2003)
The article argues that the desire for comparative literature is characteristic for "small nations." However, the comparison shows that the influence is always one-directional and that "small literatures" are measured by the standards of dominant ones. The paper therefore proposes a different approach - that of cultural comparison in which the works are not judged by influence but by contextual similarities.